2011
DOI: 10.1111/j.1600-0447.2011.01726.x
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of distinct neural systems in patients with obsessive–compulsive disorder with autogenous and reactive obsessions

Abstract: While disturbed energy metabolism in ACC might reflect a common pathology in patients with OCD regardless of symptom dimension, alterations in mesiotemporal lobe are more likely for autogenous obsessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…22, 23, 24, 26, 27, 28, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51 Of these, three studies were excluded because they did not compare metabolites between OCD patients and HC subjects. 44, 45, 46 Another study was excluded because it was a review article.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22, 23, 24, 26, 27, 28, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51 Of these, three studies were excluded because they did not compare metabolites between OCD patients and HC subjects. 44, 45, 46 Another study was excluded because it was a review article.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, 17 studies were included in the final meta-analysis. 22, 23, 24, 26, 27, 28, 31, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43 …”
Section: Resultsmentioning
confidence: 99%
“…Effects of OCD on Glu or Glx were noted in prior studies in caudate, white matter, or posterior middle cingulate (Yücel et al, 2008; Whiteside et al, 2006, 2012; Rosenberg et al, 2000, 2004). Of studies of pACC or aMCC, some (Kitamura et al, 2006; Ebert et al, 1997; Sumitani et al, 2007) did not quantify Glu or Glx; others (Yalçın et al, 2011; Bédard et al, 2011; Besiroglu et al, 2011; Fan et al, 2010) expressed results as ratios (e.g., Glx/Cr). Two studies of pACC using absolute metabolites (Lázaro et al, 2012; Simpson et al, 2012) found no effects of OCD on Glx.…”
Section: Discussionmentioning
confidence: 99%
“…In a study using proton magnetic resonance spectroscopy, patients with autogenous obsessions, which do not emerge in response to identifiable external stimuli, had elevated NAA/CR ratios in the amygdala and hippocampus. This increase was not observed in the same brain regions of healthy controls or patients with reactive obsessions, a subtype of OCD in which obsessions are evoked by specific external stimuli (Besiroglu et al, 2011). In contrast, altered energy metabolism was found in the ACC, a commonly implicated brain region in the pathology of OCD, in patients with either subtype of OCD.…”
Section: Pathology Of Ocdmentioning
confidence: 93%